The Effect of Perceptions of Technology, Risk and Handling Complaints on Customer Interest in Using Internet Banking At Bank Syari'ah Indonesia (BSI) KC Kisaran - Khoiriaturrahmah, Miftah; Anggraini, Tuti; Jannah, Nurul (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Bank Syari'ah Indonesia (BSI) is one of the companies that also utilizes information technology through digital services. Only not all digital services have many users, such as internet banking which is less than M-banking users. This study aims to determine the effect of perceived technology, risk and complaint handling on customer interest in using Internet banking at Bank Syariah Indonesia (BSI) Kisaran Branch Office. This research is a type of descriptive quantitative research. The population in this study were BSI customers at the Kisaran Branch Office. While the sample was obtained as many as 100 customers. Data collection techniques using questionnaires and documentation. The data analysis technique uses multiple regression analysis where before conducting multiple regression tests, classical assumption testing is carried out. The results of this study are Technology Perceptions, affecting customer interest in using Internet Banking at Bank Syariah Indonesia (BSI) Branch Office in Kisaran. Risk, affects customer interest in using Internet Banking at Bank Syari'ah Indonesia (BSI) Kisaran Branch Office. Handling Complaints, affects customer interest in using Internet Banking at Bank Syari'ah Indonesia (BSI),isaran Branch Office. The suggestion of this research is that it is hoped that the BSI Kisaran Branch Office will conduct broader socialization and promotion to further introduce the presence of Internet Bangking to potential customers. Keywords: Technologi Perception, Risk, Complaint Handling, Customer Interest